PENGARUH KUALITAS PRODUK, CITRA MEREK, DAN CELEBRITY ENDORSER TERHADAP NIAT BELI ULANG WARDAH KOSMETIK (Studi Kasus pada Silka Cosmetics Semarang) - Rianur Rahmawati, 15.05.51.0203; Basiya, r (Students' Journal of Economic and Management, 2019)
This study aims to examine the effect of product quality, brand image and celebrity endorser on Wardah Cosmetics repurchase interest. This research was conducted at Silka Cosmetics Semarang. Respondents in this study were 100 respondents. Sampling in this study using purposive sampling technique and accidental sampling. The data collection method in this study uses a questionnaire. Analysis using SPSS 19.0 which includes validity test, reliability test, kolmogorov smirnov normality test, multiple linear regression test, statistic f test, coefficient of determination test, and t test. The results of this study indicate that product quality and brand image have a positive effect on repurchase interest. While celebrity endorser has a negative effect on repurchasing interest.